GTH 2021 State of the Art—Cardiac Surgery: The Perioperative Management of Heparin-Induced Thrombocytopenia in Cardiac Surgery - Ranta, Laura; Scala, Emmanuelle (Hämostaseologie, 2021)
Heparin-induced thrombocytopenia (HIT) is a severe, immune-mediated, adverse drug reaction that paradoxically induces a prothrombotic state. Particularly in the setting of cardiac surgery, where full anticoagulation is required during cardiopulmonary bypass, the management of HIT can be highly challenging, and requires a multidisciplinary approach. In this short review, the different perioperative strategies to run cardiopulmonary bypass will be summarized.
Keywords: Heparin-induced thrombocytopenia; cardiac surgery; state of the art